For how long do IMF forecasts of world economic growth stay up-to-date? - Katja Heinisch; Axel Lindner (Applied Economics Letters, 2018)
This study analyses the performance of the International Monetary Fund (IMF) World Economic Outlook output forecasts for the world and for both the advanced economies and the emerging and developing economies. With a focus on the forecast for the current year and the next year, we examine the durability of IMF forecasts, looking at how much time has to pass so that IMF forecasts can be improved by using leading indicators with monthly updates. Using a real-time data set for GDP and for indicators, we find that some simple single-indicator forecasts on the basis of data that are available at higher frequency can significantly outperform the IMF forecasts as soon as the publication of the IMF's Outlook is only a few months old. In particular, there is an obvious gain using leading indicators from January to March for the forecast of the current year.
Keywords: C52; C53; E02; E32; E37; O19; 330; IMF WEO forecasts; leading indicators; real-time data